2016
DOI: 10.1002/brb3.557
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of progressive supranuclear palsy in Yonago: change throughout a decade

Abstract: BackgroundProgressive supranuclear palsy (PSP) is a neurodegenerative disorder that is sometimes confused with Parkinson's disease, multiple system atrophy, and other disorders. The typical clinical features are categorized as Richardson's syndrome (RS), but other clinical subtypes include PSP‐parkinsonism (PSP‐P) and PSP‐pure akinesia with gait freezing (PSP‐PAGF). In this study, we determined the prevalence of PSP in a Japanese rural area compared to our previous 1999 report.MethodsWe collected data in Yonag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 21 publications
5
58
0
Order By: Relevance
“…However, a study in Japan that included other PSP phenotypes in addition to PSP-RS found a total prevalence of 18 per 100,000 across all ages. 5 This higher prevalence number is consistent with estimates from autopsy series, 6 and suggests that the prevalence of the full spectrum of PSP syndromes is substantially higher than estimates based on PSP-RS alone. A cluster of PSP cases in an industrial city in France and a multicenter case-control study suggest that environmental risk factors influence PSP incidence.…”
Section: Introductionsupporting
confidence: 73%
“…However, a study in Japan that included other PSP phenotypes in addition to PSP-RS found a total prevalence of 18 per 100,000 across all ages. 5 This higher prevalence number is consistent with estimates from autopsy series, 6 and suggests that the prevalence of the full spectrum of PSP syndromes is substantially higher than estimates based on PSP-RS alone. A cluster of PSP cases in an industrial city in France and a multicenter case-control study suggest that environmental risk factors influence PSP incidence.…”
Section: Introductionsupporting
confidence: 73%
“…The analysis of gender distribution resulted in a greater proportion of the PSP diagnosis for male patients over the entire observation period with a maximum peak in 2012 with 60.6% male patients. In the analysis of Takigawa et al, comparable rates for gender distribution with more male patients affected were observed [ 16 ]. In other studies, these data were not sufficiently documented [ 16 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the analysis of Takigawa et al, comparable rates for gender distribution with more male patients affected were observed [ 16 ]. In other studies, these data were not sufficiently documented [ 16 , 20 , 21 ]. The mean age of hospitalized PSP patients only varied between 72.3 and 73.4 years over the entire period of analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These values reflect however only Richardson's syndrome (RS). In a recent study in Japan that also assessed cases with PSP and progressive gait freezing (PSP‐PGF), the prevalence of PSP was estimated at 17.9 per 100,000 . Recent estimations of incidence, ranging from 0.14 to 1.2 per 100,000 person‐years, do exist, but they also reflect the incidence of RS rather than PSP .…”
Section: Psp: Milestones Of the Recent 10 Yearsmentioning
confidence: 99%